Extraction Of Pectinase From Pectinolytic Bacteria Isolated From Carrot Waste - R. C. PATIL,; TUSHAR P. MURUGKAR,; SHAMIM A. SHAIKH, (International Journal of Pharma and Bio Sciences, 2012)
Degradation of waste especially that of vegetable waste has become a mounting challenge owing to its generation in huge amounts. This vegetable market generated waste can be utilized to biosynthesize pectinase enzyme at cheaper rate which have numerous industrial applications. Screening was carried out to obtain pectinase producing microorganisms from carrot. The best isolate was identified as a unique strain of Bacillus sp. based on morphological, biochemical tests and using 16S rRNA gene sequencing studies. This isolate was selected for further bulk production using the optimized conditions of pH 9 and temperature of 50oC to give a maximum yield of 49.58% from carrot waste.